Manufacturing method of alloy member

JP7629784B2Active Publication Date: 2025-02-14OSAKA GAS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021062173
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-31
Publication Date
2025-02-14
Estimated Expiration
2041-03-31

AI Technical Summary

Benefits of technology

【0014】 このように、基材上にコーティング被膜が形成された合金部材は、その使用環境において、あるいは予め所定の熱処理を施すことで、基材上に複合酸化被膜を得ることができる。この「複合酸化物被膜」は実質的には金属酸化物層であり、Crなどに関して拡散抑制層として良好に機能すると考えられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629784000001
    Figure 0007629784000001
  • Figure 0007629784000002
    Figure 0007629784000002
  • Figure 0007629784000003
    Figure 0007629784000003
Patent Text Reader

Abstract

To provide an alloy member that can be processed into a film at low cost, and can suppress volatilization of Cr or the like, which causes a degradation of a fuel cell, compared to the conventional high-cost material.SOLUTION: An alloy member has a coating layer at least containing three elements of Ni, Co, Mn, the coating layer formed wholly or at least partially on the surface of a substrate B of an Fe-Cr alloy.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy member that can be used in, for example, a solid oxide fuel cell, and to a method for producing the same. [Background technology]

[0002] Conventionally, the following technologies have been disclosed as heat-resistant alloy materials for use in solid oxide fuel cells (SOFCs).

[0003] Patent Document 1 discloses a material having a base material (corresponding to the substrate of the present invention) made of pure Ni, a Ni-based alloy not containing Cr, or an Fe-Ni alloy, and a coating layer (corresponding to the complex oxide layer of the present invention) made of a spinel complex oxide containing Ni and not containing Cr and at least one of Co, Cu, and Mn as metal elements, on the surface of the base material. This material is used for an interconnector.

[0004] Patent Document 2 discloses a material in which a steam oxidation prevention layer, which is made of a Mn-Cr oxide layer and a composite oxide layer containing Mn and Co, is formed on the surface of an Fe-Cr alloy material (corresponding to the substrate of the present invention) by slurry coating and oxidation treatment. This steam oxidation prevention layer (corresponding to the composite oxide layer of the present invention) is formed on the anode side of an interconnector.

[0005] Patent Document 3 discloses a material obtained by applying a slurry of a composite oxide containing Mn-Co-Cu to the surface of an Fe-Cr alloy material and then oxidizing the applied layer. This material is also intended for use in interconnectors.

[0006] Patent Document 4 discloses a separator in which the surface of a heat-resistant alloy metal is coated with a Ni-Co alloy. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-77913 A [Patent Document 2] JP 2010-250965 A [Patent Document 3] JP 2016-189243 A [Patent Document 4] JP 2012-119126 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the above conventional techniques have the following problems. If pure Ni or a Ni-based alloy not containing Cr is used for the alloy member as in Patent Document 1, the material cost will be significantly high.

[0009] When a method of applying a complex composite oxide to an alloy member to obtain a desired treatment layer is adopted as in Patent Documents 2 and 3, the manufacturing cost of the alloy member as a whole increases. Furthermore, there is also room for improvement in suppressing Cr volatilization.

[0010] In Patent Document 4, an attempt is made to obtain the desired treatment layer by coating with two elements, Ni and Co. However, coating with only these elements is unable to suppress the growth of oxide scale caused by high-temperature oxidation of the alloy material, resulting in problems in terms of durability.

[0011] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide an alloy member that can be formed into a film at low cost using a simple method, and that can suppress the volatilization of Cr and other elements that cause deterioration of fuel cells more effectively than conventional high-cost materials. [Means for solving the problem]

[0012] A first characteristic feature of the present invention is that the alloy member is an alloy member having a coating film containing at least the three elements Ni, Co and Mn formed on the entirety or at least a part of the surface of a base material of an Fe-Cr alloy.

[0013] According to this configuration, by using an Fe-Cr alloy as the substrate, it is possible to use a material that is easily available and versatile. In this way, when the substrate is an Fe-Cr alloy, the volatilization of Cr and other elements from the substrate can be a problem, but as will be shown in each example later, by forming a coating film containing at least the three elements Ni, Co, and Mn on the substrate, the volatilization of Cr and other elements that cause deterioration of fuel cells and the like can be suppressed.

[0014] In this way, the alloy member having the coating film formed on the substrate can have a composite oxide film on the substrate in the environment in which it is used or by subjecting it to a predetermined heat treatment in advance. This "composite oxide film" is essentially a metal oxide layer, and is considered to function well as a diffusion suppression layer for Cr and the like.

[0015] When the coating film is converted into a composite oxide, for example, when the alloy member according to the present invention is directly incorporated into an electrochemical device, which is an example of a solid oxide fuel cell, a heat treatment is performed at an operating temperature of 600 to 800° C. On the other hand, by performing a heat treatment (oxidation treatment) at a temperature of 600 to 1100° C. before being incorporated into the device, the metal elements contained in the coating film can generate cobalt spinel compound Co3O4, manganese spinel compound Mn3O4, cobalt manganese spinel compound (Co,Mn)3O4, nickel manganese spinel compound (Ni,Mn)3O4, nickel cobalt spinel compound (Ni,Co)3O4, nickel iron spinel compound (Ni,Fe)3O4, etc., and it becomes possible to suppress the volatilization of Cr and the like from the Fe-Cr alloy substrate.

[0016] Coating films containing the three elements Ni, Co, and Mn can be formed by plating (electrolytic plating or electroless plating), electrodeposition painting, vapor deposition, thermal spraying, etc.

[0017] The thickness of the coating film may be appropriately determined according to the dimensions of the Fe-Cr alloy substrate and the conditions of use, but for example, it is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 1.5 μm or more. This is because if the coating film is too thin, the uniformity of the film thickness decreases and the effect of suppressing Cr volatilization decreases. In addition, the film thickness is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. This is because if the film thickness is too thick, the performance of the electrochemical element decreases and problems such as high manufacturing costs occur.

[0018] A second characteristic configuration of the present invention relates to the alloy member of the present invention, The coating film is a plating film containing at least the three elements Ni, Co and Mn.

[0019] As mentioned above, the coating film containing the three elements Ni, Co, and Mn can be formed by plating, electrodeposition painting, vapor deposition, thermal spraying, etc., but from the viewpoint of uniformity of film thickness and reduction of processing time, plating is preferable. It is also inexpensive and has excellent versatility.

[0020] The Ni--Co--Mn plating film can be formed using an alloy plating solution containing sulfates, hydrochlorides, sulfamates, etc. of Ni, Co, and Mn.

[0021] A third characteristic configuration of the present invention relates to the alloy member of the present invention, The coating film is an electrodeposition coating film containing at least the three elements Ni, Co and Mn.

[0022] In electrocoating, metal oxide particles containing Ni, Co, and Mn are dispersed in an electrocoating solution containing an anionic resin such as polyacrylic acid, and an electric current is passed between the metal substrate as the positive electrode and a SUS304 counter electrode as the negative electrode, forming an electrocoating film on the surface of the metal substrate.

[0023] A fourth characteristic configuration of the present invention relates to the alloy member of the present invention, The Fe-Cr alloy substrate contains 0.05 mass % or more of Mn.

[0024] In addition to providing the high-temperature durability required for the Fe-Cr alloy substrate, this is useful for diffusing and adjusting Mn into the complex oxide film unique to the present invention. If the content is less than 0.05 mass%, this effect is difficult to obtain.

[0025] A fifth characteristic configuration of the present invention relates to the alloy member of the present invention, The Fe-Cr alloy of the substrate contains 0.05% by mass or more and 1.0% by mass or less of Ni, 0.01% by mass or more and 1.0% by mass or less of Cu, and 0.05% by mass or more and 1.0% by mass or less of Ti.

[0026] When the above-mentioned Fe-Cr based alloy is used as a substrate, it can be made into an alloy member having excellent performance and durability, and can be used for an electrochemical element.

[0027] A sixth characteristic configuration of the present invention relates to the alloy member of the present invention, The Fe-Cr alloy contains 18% by mass or more and 25% by mass or less of Cr.

[0028] When the Cr content is 18 mass % or more, the corrosion resistance of the Fe-Cr alloy is easily maintained, and when the Cr content is 25 mass % or less, the cost of the Fe-Cr alloy can be reduced.

[0029] In addition, it is preferable to use ferritic stainless steel as the Fe-Cr alloy, since it is possible to make the thermal expansion coefficient closer to that of the electrode material and electrolyte material constituting the electrochemical element. In addition, it is more preferable that the upper limit of the Cr content is 23 mass% or less.

[0030] A seventh characteristic configuration of the present invention relates to the alloy member of the present invention, The feature is that a Cr oxide layer is included between the substrate and the coating film containing at least the three elements of Ni-Co-Mn.

[0031] By adopting this configuration, the effect of suppressing the diffusion and volatilization of Cr and the like from the substrate can be obtained by the Cr oxide layer, which is preferable.

[0032] An eighth characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, The plating film is formed using a plating solution containing at least the three elements Ni, Co and Mn.

[0033] By adopting this method for manufacturing an alloy member, a plating solution containing a predetermined element can be used to easily and inexpensively produce a predetermined plating film on the surface (outer surface) of a substrate. Furthermore, it is preferable because the ratio of the predetermined element in the plating solution can be adjusted to a desired ratio. Furthermore, when a predetermined heat treatment is performed after the plating film is formed in this way, the plating film becomes a desired composite oxide film, which can suppress the volatilization of Cr and the like and also stabilize the alloy member.

[0034] A ninth characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, The present invention provides a method for producing a multi-layer plating film containing at least the three elements Ni, Co and Mn by using a plating solution containing at least one element selected from the three elements Ni, Co and Mn, and thereby obtaining the plating film.

[0035] In this manufacturing method, the plating film has a multi-layer structure. When configured in this way, the selection and concentration adjustment of elements contained in each layer can be suitably realized by using a plating solution containing predetermined elements according to the position of each layer from the substrate (whether it is the inner side located on the substrate side or the outer side of the inner side). Furthermore, the thickness of these layers can also be adjusted.

[0036] Furthermore, by carrying out a prescribed heat treatment after forming multiple plating layers in this manner, a complex oxide coating conforming to the concentration distribution of elements in each plating layer can be suitably formed through the diffusion and stabilization of each element.

[0037] A tenth characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, In the multi-layer alloy plating film formed in the above-mentioned multiple layers, the outermost layer formed on the outermost side contains Mn.

[0038] By including Mn in the outermost layer, the alloy material can be stabilized and the electrical characteristics with electrodes, etc. formed on the surface of this alloy member can be adjusted.

[0039] An eleventh characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, The multiple layers include an inner layer located on the substrate side and an outer layer located outside the inner layer, the inner layer contains at least two elements, Ni and Co, and the outer layer contains at least Mn.

[0040] In this way, by configuring the inner layer and the outer layer to contain the respective predetermined elements, the predetermined layers can be easily formed in sequence by at least two-stage plating treatment. The inner layer mainly provides the function and effect of suppressing the diffusion and volatilization of Cr and the like, and the outer layer provides the function and effect of improving the compatibility (mechanical compatibility and electrical compatibility) with layers provided on the outside and ensuring robustness.

[0041] A twelfth characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, The electrodeposition coating film is formed using an electrodeposition coating solution containing at least the three elements Ni, Co and Mn.

[0042] By adopting this manufacturing method for alloy members, a predetermined electrodeposition coating film can be easily and inexpensively manufactured on the substrate surface (outer surface) using an electrodeposition coating liquid containing a predetermined element. Furthermore, it is preferable because the ratio of the predetermined element in the electrodeposition coating liquid can be adjusted to a desired ratio. Furthermore, when a predetermined heat treatment is performed after forming the electrodeposition coating film in this way, the electrodeposition coating film becomes a desired complex oxide film, which can suppress the volatilization of Cr and the like and also stabilize the alloy member.

[0043] A thirteenth characteristic configuration of the present invention relates to a method for producing an alloy member of the present invention, The coating film is a composite oxide film formed by heat treatment.

[0044] As explained above, a composite oxide film, which can be said to be one of the objects of the present invention, can be obtained. Here, the heat treatment may be performed separately before the alloy member is used, or the alloy member may be used in a state in which a coating film is formed, and the composite oxide film of the present application may be formed during the use. In the former example, the alloy member is heat-treated before the use in various atmospheres (e.g., in air, etc.), and the heat treatment temperature may be appropriately determined according to the size of the Fe-Cr alloy base material and the thickness of the coating film. For example, the heat treatment temperature is preferably 1100°C or less, more preferably 1050°C or less, and even more preferably 1000°C or less. This is because if the heat treatment temperature is too high, the base material is easily deteriorated. In addition, for example, the heat treatment temperature is preferably 400°C or more, more preferably 500°C or more, and even more preferably 600°C or more. This is because if the heat treatment temperature is too low, it is difficult to obtain the desired composite oxide film. In the latter example, when the alloy member according to the present invention is used in an electrochemical element such as a solid oxide fuel cell or a solid oxide electrolysis cell, the operating temperature is about 650 to 900°C, so that the heat treatment can be performed in the operating state.

[0045] By carrying out the heat treatment in this manner, as described in the fourteenth characteristic configuration of the present invention, the alloy member of the present invention can have a configuration in which Ni, Co, and Mn are diffused into the plating film by the heat treatment after the plating film is formed.

[0046] As described in a fifteenth characteristic configuration of the present invention, after the coating film is formed, Mn contained in the Fe-Cr alloy can be diffused into the coating film by heat treatment.

[0047] In this way, by diffusing the Mn contained in the base material into the coating film (alloy plating film or oxide electrodeposition film) which is a complex oxide film, it is possible to increase the production amounts of manganese spinel compound Mn3O4, cobalt manganese spinel compound (Co,Mn)3O4, nickel manganese spinel compound (Ni,Mn)3O4, and the like which are useful in the present invention.

[0048] In order to increase the Mn content, it is necessary to increase the Mn concentration when forming the coating film, but if it is based only on plating, it takes time to achieve the desired film thickness, resulting in high costs. In contrast, if the Mn concentration is increased by diffusion from the substrate side after the plating film is formed, the thickness and Mn concentration of the plating film can be reduced, and a complex oxide film can be formed in a short time and at low cost.

[0049] The inventors have confirmed that the Mn content in the complex oxide coating is preferably 1% or more, more preferably 2% or more, and even more preferably 3% or more, and is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less. However, when the 15th characteristic configuration of the present invention is adopted, it becomes possible to receive Mn from the substrate side, which is particularly preferable.

[0050] Regarding the Mn content, if the content is too low, the amount of manganese spinel compound Mn3O4, cobalt manganese spinel compound (Co,Mn)3O4, nickel manganese spinel compound (Ni,Mn)3O4, etc. produced will be small, and the ability to retain Cr and other elements that diffuse and volatilize from the Fe-Cr alloy base material will tend to decrease.

[0051] [Use of alloy members] Hereinafter, the case where the alloy member according to the present invention is used as each of the constituent members constituting a solid oxide fuel cell will be described. In the following explanation, the use of the material in components such as an "electrochemical element," "metal support," "separator," "manifold," "interconnector," and "current collecting member" will be described, and the function and action of each component will be explained.

[0052] The "metal support" in the present invention is a member that basically serves as a support for constituting an "electrochemical element", and is provided with at least an electrode layer and an electrolyte layer on its outer surface, and further with a counter electrode layer on the opposite side of the electrode layer, sandwiching the electrolyte layer, to form an electrochemical element.

[0053] When this electrochemical element is used as a fuel cell, for example, the electrode layer is used as a fuel electrode layer and the counter electrode layer is used as an air electrode layer, so that electric power can be generated between the two electrodes. That is, the electrochemical element can be used as a single fuel cell by supplying a reducing gas (typically a fuel gas containing hydrogen) to the fuel electrode layer and an oxidizing gas (typically air containing oxygen) to the air electrode layer. Conversely, when a predetermined electric power is supplied between the two electrodes, the electrochemical element is capable of functioning as an electrolysis element that receives a supply of water and decomposes it.

[0054] Therefore, in the present invention, when the electrochemical element is operated as a fuel cell, the electrochemical device becomes a fuel cell device, and when the electrochemical element is operated as an electrolysis cell, the electrolysis device becomes an electrolysis device.

[0055] Generally, when constructing a fuel cell device, a large number of electrochemical elements that function as single fuel cell cells are stacked together to collect the electricity generated by each single cell, and the "collecting member" is a member used to collect the electricity generated by the single cell.

[0056] In a structure in which many single cells are stacked, it is necessary to supply a specific gas to each electrode (electrode layer and counter electrode layer), and the member that separates these gas flow paths is called a "separator." Meanwhile, the distribution mechanism for supplying a specific gas to the gas flow paths that are provided independently on either side of the "separator" is called a "manifold."

[0057] The following will explain each in order. As a sixteenth characteristic configuration of the present invention, an electrochemical element can be formed by providing at least an electrode layer, an electrolyte layer and a counter electrode layer on the alloy member described thus far.

[0058] In an electrochemical element in which at least an electrode layer, an electrolyte layer, and a counter electrode layer are provided on the above-mentioned alloy member, the volatilization of Cr and the like from the alloy member is suppressed, and the generation of oxide scale is also suppressed, resulting in a high-performance electrochemical element.

[0059] Furthermore, for example, the thermal expansion coefficient of the zirconia-based or ceria-based materials contained in the electrode layer materials and electrolyte layer materials of SOFCs can be made close to the thermal expansion coefficient of the Fe-Cr-based alloy. Therefore, even when the electrochemical element is used at high temperatures or subjected to a heat cycle, cracking or peeling of the electrode layer and electrolyte layer can be suppressed, resulting in a highly reliable electrochemical element.

[0060] Here, according to a twenty-second characteristic configuration of the present invention, a solid oxide fuel cell can be configured in which an electric power generating reaction occurs using an electrochemical element of this configuration.

[0061] Here, according to a twenty-third characteristic configuration of the present invention, a solid oxide electrolysis cell in which an electrolytic reaction occurs can be configured using an electrochemical element of this configuration.

[0062] According to the above characteristic configuration, it is possible to suppress the deterioration of the electrochemical element and maintain the performance of the fuel cell for a long period of time. In addition, a solid oxide fuel cell that can be operated at a temperature range of 650°C or more during rated operation is more preferable because it can construct a fuel cell system that uses a hydrocarbon gas such as city gas as a raw fuel and can cover the heat required for converting the raw fuel into hydrogen with the exhaust heat of the fuel cell, thereby improving the power generation efficiency of the fuel cell system. In addition, a solid oxide fuel cell that is operated at a temperature range of 900°C or less during rated operation is more preferable because it can maintain a high effect of suppressing the volatilization of Cr and the like and can be made to have excellent long-term durability, and a solid oxide fuel cell that is operated at a temperature range of 850°C or less during rated operation is even more preferable because it can further enhance the effect of suppressing the volatilization of Cr and the like and can be made to have excellent long-term durability. In addition, the formation of oxide scale can be suppressed.

[0063] As a seventeenth characteristic configuration of the present invention, an electrochemical module can be formed in which a plurality of the above-mentioned electrochemical elements are arranged in a group state.

[0064] According to the above characteristic configuration, a plurality of the above-mentioned electrochemical elements are arranged in a cluster, so that a compact, high-performance electrochemical module having excellent strength and reliability can be obtained while keeping material costs and processing costs down.

[0065] An 18th characteristic configuration of the present invention can be an electrochemical device having an electrochemical element or electrochemical module as described above, and a fuel converter that circulates a gas containing a reducing gas to the electrochemical element or the electrochemical module, or a fuel converter that converts a gas containing a reducing component generated in the electrochemical element or the electrochemical module.

[0066] According to the above characteristic configuration, when the electrochemical element or electrochemical module is operated as a fuel cell, hydrogen can be generated from natural gas or the like supplied using existing raw fuel supply infrastructure such as city gas by a fuel converter such as a reformer, and the hydrogen can be circulated to the fuel cell. Also, when the electrochemical element or electrochemical module is operated as an electrolysis cell, for example, it can be an electrochemical device in which hydrogen generated by the electrolysis reaction of water is reacted with carbon monoxide or carbon dioxide in a fuel converter to convert it into methane or the like.

[0067] An electrochemical device that operates according to the above principle is configured to have at least an electrochemical element or electrochemical module, and a power converter that extracts power from the electrochemical element or electrochemical module or that supplies power to the electrochemical element or electrochemical module, as described in the 19th characteristic configuration of the present invention.

[0068] That is, when the power converter performs a power extraction operation, the power generated by these elements or modules is extracted.

[0069] On the other hand, when the power converter is operating to supply power, electrolysis can be performed in these elements or modules. For example, water vapor and carbon dioxide can be supplied to these elements or modules and electrolyzed to produce hydrogen and carbon monoxide. When such a configuration is adopted, it is preferable to provide the power converter with an inverter or the like to boost the voltage or convert direct current to alternating current, thereby enabling the desired function to be achieved.

[0070] In any case, by using the alloy member of the present invention, it is possible to realize an electrochemical device including an electrochemical element or an electrochemical module that is excellent in durability, reliability and performance.

[0071] As a twenty-first characteristic configuration of the present invention, an energy system can be configured having the electrochemical device described above and a waste heat utilization section that reuses heat discharged from the electrochemical device.

[0072] According to the above characteristic configuration, since it has an electrochemical device and a waste heat utilization unit that reuses heat discharged from the electrochemical device, it is possible to realize an energy system that is excellent in durability, reliability, and performance as well as energy efficiency. Note that it is also possible to realize a hybrid system with excellent energy efficiency by combining it with a power generation system that generates power by utilizing the combustion heat of unused fuel gas discharged from the electrochemical device.

[0073] As described in the twentieth characteristic configuration of the present invention, any of the components of an electrochemical device, that is, a separator, a manifold, an interconnector, and a current collecting member, can be formed using the alloy members described above.

[0074] If the electrochemical device has a separator and the separator is the above-mentioned alloy member, it is preferable because the volatilization of Cr and the like from the separator is suppressed. The separator is a member that separates the fuel gas flow path from the air flow path when a reducing gas (typically a fuel gas) and an oxidizing gas (typically air) are supplied to a plurality of assembled electrochemical elements.

[0075] If the electrochemical device has a manifold and the manifold is made of the above-mentioned alloy member, it is preferable because the volatilization of Cr and the like from the manifold is suppressed. Note that the manifold is a member that supplies a reducing gas (typically a fuel gas) or an oxidizing gas (typically air) to a plurality of assembled electrochemical elements.

[0076] If the electrochemical device has an interconnector and the interconnector is the above-mentioned alloy member, it is preferable because the volatilization of Cr and the like from the interconnector is suppressed. Note that the interconnector is a member that joins a plurality of electrochemical elements.

[0077] The electrochemical device has a current collecting member, and if the current collecting member is the above-mentioned alloy member, it is preferable because the volatilization of Cr and the like from the current collecting member is suppressed. The current collecting member is a member that has electronic conductivity and is connected to the electrode layer of the electrochemical element. [Brief description of the drawings]

[0078] [Figure 1] A diagram showing the state of coating film formation on a test piece. [Diagram 2] FIG. 1 is a diagram showing line profiles of Ni, Co, and Mn in the alloy member of Example 1. [Diagram 3] FIG. 1 is a diagram showing line profiles of Cr and Fe in the alloy member of Example 1. [Figure 4] FIG. 1 is a diagram showing line profiles of Ni, Co, and Mn after a high-temperature test in a cathodic atmosphere of the alloy member of Example 1. [Diagram 5] FIG. 1 shows line profiles of Cr and Fe after high temperature testing in a cathodic atmosphere for the alloy member of Example 1. [Figure 6] FIG. 1 is a diagram showing line profiles of Ni, Co, and Mn after high-temperature testing in an anodic atmosphere of the alloy member of Example 1. [Figure 7] FIG. 1 is a diagram showing line profiles of Cr and Fe after high-temperature testing in an anodic atmosphere for the alloy member of Example 1. [Figure 8] FIG. 1 is a diagram showing line profiles of Ni, Co, and Mn in the alloy member of Example 2. [Figure 9] FIG. 1 shows line profiles of Cr and Fe in the alloy member of Example 2. [Figure 10] FIG. 1 shows line profiles of Ni, Co, and Mn after high temperature testing in a cathodic atmosphere for the alloy member of Example 2. [Figure 11] FIG. 1 shows line profiles of Cr and Fe after high temperature testing in a cathodic atmosphere for the alloy member of Example 2. [Figure 12] FIG. 1 shows line profiles of Ni, Co, and Mn after high-temperature testing in an anodic atmosphere of the alloy member of Example 2. [Figure 13] FIG. 1 shows line profiles of Cr and Fe after high-temperature testing in an anodic atmosphere for the alloy member of Example 2. [Figure 14] FIG. 1 shows line profiles of Ni, Co, and Mn in the alloy member of Example 3. [Figure 15] FIG. 1 shows line profiles of Cr and Fe in the alloy member of Example 3. [Figure 16] FIG. 13 is a diagram showing line profiles of Ni, Co, and Mn after a high-temperature test in a cathodic atmosphere of the alloy member of Example 3. [Figure 17] FIG. 13 is a diagram showing line profiles of Cr and Fe after a high-temperature test in a cathodic atmosphere for the alloy member of Example 3. [Figure 18] FIG. 13 is a diagram showing line profiles of Ni, Co, and Mn after high-temperature testing in an anodic atmosphere of the alloy member of Example 3. [Figure 19] FIG. 13 is a diagram showing line profiles of Cr and Fe after high-temperature testing in an anodic atmosphere for the alloy member of Example 3. [Figure 20] FIG. 1 shows the results of contact resistance (ASR) measurement for Example 4, Example 5, and Comparative Example 2. [Figure 21] A cross-sectional view showing a configuration example of an electrochemical element. [Figure 22] A diagram showing an example of the configuration of an electrochemical module. [Figure 23] FIG. 1 shows an example of the configuration of an electrochemical device that functions as a fuel cell device. [Figure 24] FIG. 1 shows another example of the configuration of an electrochemical module. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0079] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.

[0080] [Alloy member and manufacturing method thereof] The alloy member according to the present invention is constructed by forming a coating film containing at least the three elements Ni, Co, and Mn on the entire or at least a part of the surface of a substrate made of an Fe-Cr alloy, which contains Mn.

[0081] The coating film can be manufactured by forming a coating film containing the three elements Ni, Co, and Mn on the surface of the substrate. Coating methods include plating (electrolytic plating and electroless plating), electrodeposition painting, vapor deposition, and thermal spraying. The coating may be carried out in one step or in multiple steps.

[0082] The coating film formed on the substrate as described above is heat-treated in an oxidizing atmosphere. The heat treatment temperature can be 600° C. to 1000° C., and the heat treatment may be performed when the alloy member is assembled into an apparatus as a predetermined functional part, or may be performed on the alloy member alone at a previous stage. This type of heat treatment promotes integration of the Fe-Cr alloy with the coating film, and also promotes alloying of the elements contained in the coating film, while preventing diffusion of Cr and other elements in the substrate to the outer surface and volatilization outside the component.

[0083] [Use of alloy members] The alloy member manufactured according to the above-mentioned method can suppress the diffusion and volatilization of Cr and the like even when exposed to a high-temperature oxidizing atmosphere, and is therefore suitable for use in the electrochemical element, electrochemical device, solid oxide fuel cell, and the like referred to in the present invention.

[0084] Hereinafter, the examples will be described in the order of "Alloy members, their production and evaluation" and "Use forms of the alloy members".

[0085] [Alloy components, their manufacture and evaluation] The examples are examples in which a coating film is produced by plating, and the composite oxide film desired in the present invention can be obtained by heat treating the plating layer formed by plating in an oxidizing atmosphere. In Examples 1, 2, and 4, as shown in Fig. 1(a), a plating film b is formed on the surface of a substrate B by a one-stage alloy plating process, and then this plating film b is made into a composite oxide film through a specified heat treatment. In these Examples, the process of forming the plating film b is the same. However, Example 1 is an example in which a high-temperature exposure test was performed without any particular heat treatment, and Example 2 is an example in which a heat treatment was performed in an oxidizing atmosphere before the high-temperature exposure test.

[0086] The element profiles of these examples are shown in Figure 2 for Ni, Co, and Mn in Example 1, and in Figure 3 for Cr and Fe on the substrate side. The elements of Ni, Co, and Mn in Example 2 are shown in Figure 8, and the elements of Cr and Fe on the substrate side are shown in Figure 9.

[0087] Example 3 is an example in which, as shown in FIG. 1(b), a two-layer plating film b (b1, b2) is formed on the surface of the base material B by a two-stage plating process, and this multi-layer plating film is made into a composite oxide film through a specified heat treatment. The element profiles of Example 3 are shown in FIG. 14 for Ni, Co, and Mn, and in FIG. 15 for Cr and Fe on the substrate side.

[0088] Example 5 is an example in which an electrodeposition coating film b is formed on the surface of a substrate B by electrodeposition coating, and then this electrodeposition coating film b is turned into a composite oxide coating film through a specified heat treatment. As in Example 4, the contact resistance (area surface resistance) evaluation is shown in FIG.

[0089] The substrate, plating, and heat treatment will be described in that order below, and the results of high temperature exposure tests carried out on each example will also be described. Here, the base material B is common to all the embodiments. Furthermore, in the plating, the pretreatment (alkaline degreasing treatment and Ni strike plating treatment) performed before the main plating treatment containing the three elements Ni, Co, and Mn is also common to all the embodiments.

[0090] 1. Base material A test piece (φ25×0.3 mm) made of an Fe—Cr alloy having the following composition was used as the substrate B. The composition values ​​are in mass %. Si:0.094, Mn:0.17, Cu:0.43, Ni:0.18, Cr:20.82, P:0.03, Al:0.04, Mo:0.053, Nb:0.008, Ti:0.325, balance: Fe

[0091] 2. Plating The plating was carried out by carrying out an alkaline degreasing treatment as a pretreatment, followed by Ni strike plating, also as a pretreatment, and then carrying out the main plating.

[0092] 2-1 Alkaline degreasing treatment The alkaline degreasing solution used in this treatment was as follows: Sodium hydroxide 20g / L Sodium silicate 20g / L Sodium phosphate 20g / L Sodium dodecyl sulfate 1g / L

[0093] The test piece, which is the substrate B, is fixed to a plating jig and immersed in an alkaline degreasing solution at 50°C and a cathode current density of 5A / dm 2 The plate was subjected to alkaline degreasing treatment for 2 minutes.

[0094] 2-2 Ni strike plating treatment The Ni strike plating solution used in this treatment is as follows: Nickel chloride hexahydrate 240g / L 37% hydrochloric acid 120g / L

[0095] After the alkaline degreasing treatment, the test piece was washed with water and then immersed in Ni strike plating solution at 25°C and a cathode current density of 5A / dm 2 The plating was carried out for 2 minutes.

[0096] 2-3 Plating and evaluation results for each example The plating method and the evaluation results of the obtained alloy members will be described below in the order of Examples 1, 2, and 3.

[0097] Example 1 The following chemicals were dissolved in ion-exchanged water to prepare a Ni-Co-Mn alloy plating solution. Ni-Co-Mn alloy plating solution Nickel sulfamate tetrahydrate 60g / L Cobalt sulfamate tetrahydrate 15g / L Manganese sulfamate tetrahydrate 407g / L Boric acid 30g / L

[0098] After the Ni strike plating, the test pieces were washed with water and then immersed in a Ni-Co-Mn alloy plating solution at 40°C, pH 4.0, and a cathode current density of 6 A / dm 2 The plating process was carried out for 10 minutes under the above conditions.

[0099] The surface composition of the plating film (alloy plating film) was analyzed by an X-ray microanalyzer (EPMA), and was found to be Ni: 56 mass %, Co: 35 mass %, and Mn: 4 mass %.

[0100] Figures 2 and 3 show the element distribution (Ni, Co, Mn, Cr, Fe) in the cross section of the alloy material. The left side is the surface side, and the right side is the back side of the substrate. In these figures, the horizontal axis is in mm (same as in Figures 4 to 19). It can be seen that Ni, Co, and Mn are distributed almost uniformly from positions 0.001 to 0.004. Cr and Fe are distributed almost uniformly deeper than 0.004 (right side). From the above element distribution results, it is recognized that in the alloy member according to this embodiment, a plated coating of Ni--Co--Mn is formed in the vicinity of the surface of the base material B.

[0101] High temperature exposure test in a cathodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in a humidified air atmosphere at 20℃, the amount of Cr volatilized was below the lower limit of quantification. No particular oxide scale was observed on the surface of the plating film. Figures 4 and 5 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure tests in a cathodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.006 to 0.014. Ni and Co are also distributed diffusely in the Fe-Cr alloy at positions 0.014 to 0.045. Cr is distributed in large amounts at positions 0.012 to 0.015, but is blocked by the Ni-Co-Mn alloy plating layer, which is consistent with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0102] High temperature exposure test in an anodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in an 80% water vapor-20% hydrogen atmosphere, the amount of Cr volatilized was below the lower limit of quantification. No particular discoloration or damage was observed on the surface of the plating film. Figures 6 and 7 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure tests in an anodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.006 to 0.014. Ni and Co are also diffused and distributed in the Fe-Cr alloy at positions 0.014 to 0.045. Cr is distributed in large amounts at positions 0.008 to 0.013, but is blocked by the Ni-Co-Mn alloy plating layer, which coincides with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0103] Example 2 A test piece plated with an Ni-Co-Mn alloy similar to that in Example 1 was placed in an electric furnace and treated at 800° C. in an air atmosphere for 1 hour.

[0104] The surface composition of the plating film was analyzed by an X-ray microanalyzer (EPMA), and the results were Ni: 12 mass %, Co: 68 mass %, and Mn: 1 mass %.

[0105] Figures 8 and 9 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the plating film by EPMA. The left side is the surface side and the right side is the substrate side. Co diffuses to the surface side (near position 0.002) and forms a Co-enriched layer, followed by Ni and Mn-enriched layers (near position 0.003 for Ni and near 0.004 for Mn). A Ni-Co-Mn alloy layer is formed from positions 0.0016 to 0.016. The Cr contained in substrate B diffuses into the Ni-Co-Mn alloy plating layer but is blocked by the Mn-enriched layer (it remains deeper than position 0.004).

[0106] High temperature exposure test in a cathodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in a humidified air atmosphere at 20℃, the amount of Cr volatilized was below the lower limit of quantification. No particular oxide scale was observed on the surface of the plating film. Figures 10 and 11 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure tests in a cathodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.002 to 0.011. Ni and Co are also diffused and distributed in the Fe-Cr alloy at positions 0.011 to 0.045. Cr is distributed in large amounts at positions 0.009 to 0.013, but is blocked by the Ni-Co-Mn alloy plating layer, which is consistent with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0107] High temperature exposure test in an anodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in an 80% water vapor-20% hydrogen atmosphere, the amount of Cr volatilized was below the lower limit of quantification. No particular discoloration or damage was observed on the surface of the plating film. Figures 12 and 13 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure testing in an anodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.006 to 0.013. Ni and Co are also diffused and distributed in the Fe-Cr alloy at positions 0.013 to 0.045. Cr is distributed in large amounts at positions 0.007 to 0.014, but is blocked by the Ni-Co-Mn alloy plating layer, which coincides with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0108] Example 3 This embodiment is an example in which plating is performed in multiple stages (specifically, two stages). In the following description, the plating applied to the substrate B side is called the inner plating, and the plating applied to the outer surface side is called the outer plating. In this example, the inner plating is Ni-Co alloy plating, and the outer plating is Mn plating. In producing the plating solutions, the following chemicals were dissolved in ion-exchanged water to prepare a Ni-Co alloy plating solution and a Mn plating solution.

[0109] a.Inner plating The following chemicals were dissolved in ion-exchanged water to prepare a Ni-Co plating solution. Nickel sulfate hexahydrate 210g / L Cobalt sulfate heptahydrate 112g / L Boric acid 35g / L

[0110] b. Outer plating The following chemicals were dissolved in ion-exchanged water to prepare a Mn plating solution. Manganese sulfate pentahydrate 200g / L Ammonium sulfate 100g / L

[0111] After Ni strike plating, the test piece was washed with water and then immersed in Ni-Co alloy plating solution at 40°C, pH 4.0, and cathode current density 3A / dm 2 The plating treatment was carried out for 20 minutes under the conditions of 30°C, pH 2.0, and cathode current density 15 A / dm. 2 The plating process was carried out for 7 minutes and 30 seconds under the above conditions.

[0112] Thereafter, the test pieces were heat-treated in an electric furnace in an air atmosphere at 800° C. for 1 hour.

[0113] The surface composition of the plating film was analyzed by an X-ray microanalyzer (EPMA), and the results were Ni: 1 mass %, Co: 4 mass %, and Mn: 63 mass %.

[0114] Figures 14 and 15 show the element distribution (Ni, Co, Mn, Cr, Fe) of the test piece cross section by EPMA. The left side is the surface side, and the right side is the substrate side. Mn diffuses from the surface into the Ni-Co layer, forming a Ni-Co-Mn alloy layer at positions 0.007 to 0.025. The Cr contained in the base material B diffuses into the Ni-Co-Mn alloy plating layer, but is blocked by the Ni-Co-Mn alloy plating layer (it remains deeper than the position 0.0012).

[0115] High temperature exposure test in a cathodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in a humidified air atmosphere at 20℃, the amount of Cr volatilized was below the lower limit of quantification. No particular oxide scale was observed on the surface of the plating film. Figures 16 and 17 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure tests in a cathodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.002 to 0.015. Ni and Co are also distributed diffusely in the Fe-Cr alloy at positions 0.016 to 0.045. Cr is distributed in large amounts at positions 0.013 to 0.018, but is blocked by the Ni-Co-Mn alloy plating layer, which is consistent with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0116] High temperature exposure test in an anodic atmosphere When a high-temperature exposure test was conducted at 850℃ for 100 hours in an 80% water vapor-20% hydrogen atmosphere, the amount of Cr volatilized was below the lower limit of quantification. No particular discoloration or damage was observed on the surface of the plating film. Figures 18 and 19 show the element distribution (Ni, Co, Mn, Cr, Fe) of the cross section of the alloy material after high-temperature exposure testing in an anodic atmosphere. It can be seen that Ni, Co, and Mn are distributed at positions 0.007 to 0.013. Ni and Co are also distributed diffusely in the Fe-Cr alloy at positions 0.013 to 0.045. Cr is distributed in large amounts at positions 0.011 to 0.014, but is blocked by the Ni-Co-Mn alloy plating layer, which is consistent with the result that the amount of Cr volatilization was below the lower limit of quantification.

[0117] Example 4 Using the same Ni-Co-Mn alloy plating solution as in Example 1, a test piece (25×25×0.3 mm) made of the same Fe-Cr alloy as in Example 1 was plated with Ni-Co-Mn alloy. The test piece was treated in an air atmosphere at 900°C for 1 hour to evaluate the area surface resistance. 1.5 Mn 1.5 The contact resistance was measured using O4 and baked at 750° C. The results are shown in Figure 20. The contact resistance was lower than that of the Co-Mn electrodeposition coating film of Comparative Example 2, which was a good result.

[0118] Example 5 Ni in ion-exchanged water0.5 Co2Mn 0.5 An electrodeposition coating solution was prepared by dispersing 100 g of O4 fine particles and 100 g of anionic polyacrylic resin. At an electrodeposition solution temperature of 30°C, a test piece (25 × 25 × 0.3 mm) made of the same Fe-Cr alloy as in Example 1 was used as the positive electrode, and a SUS304 counter electrode was used as the negative electrode. Electricity was then applied (applied voltage of 10 V, voltage application time of 10 minutes) to form an uncured Ni-Co-Mn electrodeposition coating film on the surface of the metal substrate. The test piece was treated in an air atmosphere at 900°C for 1 hour to evaluate the area surface resistance. 1.5 Mn 1.5 The contact resistance was measured using O4 and baked at 750° C. The results are shown in Figure 20. The contact resistance was lower than that of the Co-Mn electrodeposition coating film of Comparative Example 2, which was a good result.

[0119] Comparative Example 1 High temperature exposure test in a cathodic atmosphere When the test pieces were subjected to a high-temperature exposure test at 850℃ for 100 hours in a humidified air atmosphere at 20℃, the amount of Cr volatilized was 21μg / cm2, and oxide scale was formed on the surface of the test pieces.

[0120] High temperature exposure test in an anodic atmosphere When the test piece was subjected to a high-temperature exposure test at 850℃ for 100 hours in an 80% water vapor-20% hydrogen atmosphere, the amount of Cr volatilized was below the lower limit of quantification.The surface of the test piece had turned black and become rough.

[0121] Comparative Example 2 An electrodeposition coating solution was prepared by dispersing 100 g of Co2MnO4 oxide particles and 100 g of anionic polyacrylic resin in ion-exchanged water. At an electrodeposition solution temperature of 30°C, a test piece (25 × 25 × 0.3 mm) made of the same Fe-Cr alloy as in Example 1 was used as the positive electrode, and a SUS304 counter electrode was used as the negative electrode. Electricity was then applied (applied voltage of 10 V, voltage application time of 10 minutes) to form an uncured Co-Mn electrodeposition coating film on the surface of the metal substrate. The test piece was treated in an air atmosphere at 1000°C for 1 hour to evaluate the contact resistance (area surface resistance). 1.5 Mn 1.5 O4 was used and the baking treatment was performed at 750° C. The measurement results of the contact resistance are shown in FIG.

[0122] [Use of alloy members] Hereinafter, the above-mentioned alloy member will be described as a constituent member of an electrochemical element E, and further, a solid oxide fuel cell including this electrochemical element E will be described with reference to the drawings. In this solid oxide fuel cell, the alloy members according to the present invention can be used for the metal substrate 1, separator (U-shaped member 7), manifold (gas manifold 17), interconnector (cell-to-cell connection member 71), and current collecting member 26 that constitute the electrochemical element E, as described below.

[0123] The electrochemical element E is used, for example, as a component of a solid oxide fuel cell that generates electricity when supplied with a fuel gas containing hydrogen and air. In the following description of the electrochemical element E, when describing the positional relationship of layers, the electrolyte layer 4 is used as the reference layer, and the side of the counter electrode layer 6 as viewed from the electrolyte layer 4 may be referred to as the "top" or "upper side" (upper side in FIG. 21), and the side of the electrode layer 2 may be referred to as the "bottom" or "lower side". In addition, the side of the metal substrate 1 on which the electrode layer 2 is formed (upper side in FIG. 21) may be referred to as the "front side", and the opposite side (lower side in FIG. 21) may be referred to as the "back side".

[0124] (Electrochemical element) 21, the electrochemical element E has a metal substrate 1 (an example of a metal support), an electrode layer 2 formed on the metal substrate 1, an intermediate layer 3 formed on the electrode layer 2, and an electrolyte layer 4 formed on the intermediate layer 3. The electrochemical element E further has a reaction prevention layer 5 formed on the electrolyte layer 4, and a counter electrode layer 6 formed on the reaction prevention layer 5. In other words, the counter electrode layer 6 is formed on the electrolyte layer 4, and the reaction prevention layer 5 is formed between the electrolyte layer 4 and the counter electrode layer 6. The electrode layer 2 is porous, and the electrolyte layer 4 is dense.

[0125] As explained above, with regard to the layers constituting the electrochemical element E, the main element components are the electrolyte layer 4, the electrode layer 2 and the counter electrode layer 6 sandwiched therebetween, and the provision of these three layers enables the element to function as an electrochemical element.

[0126] (Metal substrate) The metal substrate 1 serves as a support that supports the electrode layer 2, the intermediate layer 3, the electrolyte layer 4, etc., and maintains the strength of the electrochemical element E. In this example, a plate-shaped metal substrate 1 is used as the metal support, but other shapes, such as a box shape or a cylindrical shape, are also possible. The metal substrate 1 need only have sufficient strength to form the electrochemical element E as a support, and may have a thickness of, for example, about 0.1 mm to 2 mm, preferably about 0.1 mm to 1 mm, and more preferably about 0.1 mm to 0.5 mm.

[0127] The metal substrate 1 has a plurality of through holes 1a that penetrate the front and back surfaces. For example, the through holes 1a can be provided in the metal substrate 1 by mechanical, chemical, or optical drilling. The through holes 1a have a function of allowing gas to pass from the back surface to the front surface of the metal substrate 1. It is also possible to use a porous metal to give the metal substrate 1 gas permeability. For example, the metal substrate 1 can be made of a sintered metal or a foam metal. As shown in FIG. 21, a coating 1b is formed on the front and back surfaces of the metal substrate 1 and on the surfaces of the through holes 1a, and this coating 1b is a composite oxide coating made of a Ni-Co-Mn alloy according to the present invention.

[0128] By using a ferritic stainless steel material (an example of an Fe-Cr alloy) as the material of the base material of the metal substrate 1, the thermal expansion coefficient is close to that of YSZ (yttria-stabilized zirconia) or GDC (gadolinium-doped ceria, also called CGO) used as the material of the electrode layer 2 and the electrolyte layer 4. Therefore, the electrochemical element E is not easily damaged even when a temperature cycle of low and high temperatures is repeated. Therefore, it is preferable because an electrochemical element E excellent in long-term durability can be realized. In addition, the Fe-Cr alloy used as the base material of the metal substrate 1 preferably contains 18% by mass or more and 25% by mass or less of Cr, preferably contains 0.05% by mass or more of Mn, and preferably contains 0.05% by mass or more and 1.0% by mass or less of Ni. In addition, the lower limit of Cu is preferably 0.01% by mass or more, more preferably 0.10% by mass or more, and even more preferably 0.20% by mass or more, and the upper limit is preferably 1.0% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.8% by mass or less. In addition, the lower limit of Ti is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and even more preferably 0.15% by mass or more, and the upper limit is preferably 1.0% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.8% by mass or less. When such an Fe-Cr-based alloy is used as a substrate, it is possible to obtain an alloy member having excellent performance, durability, and corrosion resistance while suppressing costs, and to provide it for an electrochemical element.

[0129] (electrode layer) As shown in FIG. 21, the electrode layer 2 can be provided in a thin layer state on the front surface of the metal substrate 1 in an area larger than the area where the through holes 1a are provided. When the electrode layer 2 is a thin layer, the thickness can be, for example, about 1 μm to 100 μm, preferably 5 μm to 50 μm. With such a thickness, it is possible to ensure sufficient electrode performance while reducing the amount of expensive electrode layer material used to reduce costs. The entire area where the through holes 1a are provided is covered with the electrode layer 2. That is, the through holes 1a are formed inside the area of ​​the metal substrate 1 where the electrode layer 2 is formed. In other words, all the through holes 1a are provided facing the electrode layer 2.

[0130] The material of the electrode layer 2 may be, for example, a composite material such as NiO-GDC, Ni-GDC, NiO-YSZ, Ni-YSZ, CuO-CeO2, or Cu-CeO2. In these examples, YSZ, GDC, YSZ, and CeO2 may be called aggregates of the composite material. The electrode layer 2 is preferably formed by a low-temperature firing method (for example, a wet method using firing in a low-temperature range without firing in a high-temperature range higher than 1100°C), a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method. By using these processes that can be used in a low-temperature range, a good electrode layer 2 can be obtained without firing in a high-temperature range higher than 1100°C. This is preferable because it is possible to realize an electrochemical element having excellent durability without damaging the metal substrate 1 and suppressing interdiffusion of elements between the metal substrate 1 and the electrode layer 2. Furthermore, the use of a low-temperature firing method is even more preferable because it makes it easier to handle the raw materials.

[0131] The electrode layer 2 has a plurality of pores inside and on the surface thereof to provide gas permeability. That is, the electrode layer 2 is formed as a porous layer. The electrode layer 2 is formed, for example, so that its density is 30% or more and less than 80%. The size of the pores can be appropriately selected so that the electrochemical reaction proceeds smoothly. Note that the density is the ratio of the space occupied by the material constituting the layer, and can be expressed as (1-porosity), and is equivalent to the relative density.

[0132] (Middle class) As shown in FIG. 21, the intermediate layer 3 can be formed as a thin layer on the electrode layer 2 while covering the electrode layer 2. When the intermediate layer 3 is a thin layer, the thickness can be, for example, about 1 μm to 100 μm, preferably about 2 μm to 50 μm, and more preferably about 4 μm to 25 μm. With such a thickness, it is possible to reduce the amount of expensive intermediate layer material used to reduce costs while ensuring sufficient performance. As the material for the intermediate layer 3, for example, YSZ (yttria-stabilized zirconia), SSZ (scandia-stabilized zirconia), GDC (gadolinium-doped ceria), YDC (yttrium-doped ceria), SDC (samarium-doped ceria), etc. can be used. In particular, ceria-based ceramics are preferably used.

[0133] The intermediate layer 3 is preferably formed by a low-temperature firing method (e.g., a wet method using firing in a low-temperature range without firing in a high-temperature range higher than 1100°C), a spray coating method (thermal spraying, aerosol deposition, aerosol gas deposition, powder jet deposition, particle jet deposition, cold spray, etc.), a PVD method (sputtering, pulse laser deposition, etc.), a CVD method, etc. By using these film formation processes that can be used in a low-temperature range, the intermediate layer 3 can be obtained without firing in a high-temperature range higher than 1100°C, for example. Therefore, it is possible to suppress interdiffusion of elements between the metal substrate 1 and the electrode layer 2 without damaging the metal substrate 1, and to realize an electrochemical element E with excellent durability. In addition, it is more preferable to use a low-temperature firing method because it makes it easier to handle the raw materials.

[0134] The intermediate layer 3 preferably has oxygen ion (oxide ion) conductivity. It is more preferable that the intermediate layer 3 has mixed conductivity of oxygen ions (oxide ions) and electrons. The intermediate layer 3 having these properties is suitable for application to the electrochemical element E.

[0135] (electrolyte layer) As shown in Fig. 21, the electrolyte layer 4 is formed in a thin layer state on the intermediate layer 3, covering the electrode layer 2 and the intermediate layer 3. It may also be formed in a thin film state with a thickness of 10 µm or less. More specifically, the electrolyte layer 4 is provided across (straddling) the intermediate layer 3 and the metal substrate 1. By configuring in this way and joining the electrolyte layer 4 to the metal substrate 1, the electrochemical element as a whole can be made to have excellent robustness. The electrolyte layer 4 is provided on the front surface of the metal substrate 1 in an area larger than the area in which the through hole 1a is provided. In other words, the through hole 1a is formed inside the area of ​​the metal substrate 1 in which the electrolyte layer 4 is formed.

[0136] Additionally, gas leakage from the electrode layer 2 and intermediate layer 3 can be suppressed around the electrolyte layer 4. In other words, when the electrochemical element E is used as a component of an SOFC, gas is supplied to the electrode layer 2 from the back side of the metal substrate 1 through the through-hole 1a during operation of the SOFC. In the area where the electrolyte layer 4 contacts the metal substrate 1, gas leakage can be suppressed without providing a separate member such as a gasket. Note that, although the electrolyte layer 4 covers the entire periphery of the electrode layer 2 in this embodiment, a configuration in which the electrolyte layer 4 is provided on top of the electrode layer 2 and intermediate layer 3 and a gasket or the like is provided around the periphery may also be used.

[0137] As the material of the electrolyte layer 4, YSZ (yttria-stabilized zirconia), SSZ (scandia-stabilized zirconia), GDC (gadolinium-doped ceria), YDC (yttrium-doped ceria), SDC (samarium-doped ceria), LSGM (strontium-magnesium-doped lanthanum gallate), etc. can be used. In particular, zirconia-based ceramics are preferably used. When the electrolyte layer 4 is made of zirconia-based ceramics, the operating temperature of the SOFC using the electrochemical element E can be made higher than that of the ceria-based ceramics. For example, when the electrochemical element E is used in an SOFC, a material that can exhibit high electrolyte performance even in a high temperature range of about 650°C or higher, such as YSZ, is used as the material of the electrolyte layer 4, and a hydrocarbon-based raw fuel such as city gas or LPG is used as the raw fuel of the system, and the raw fuel is converted into the anode gas of the SOFC by steam reforming or the like. In this way, a highly efficient SOFC system can be constructed in which the heat generated in the cell stack of the SOFC is used to reform the raw fuel gas.

[0138] The electrolyte layer 4 is preferably formed by a low-temperature firing method (for example, a wet method using firing in a low-temperature range without firing in a high-temperature range exceeding 1100°C), but can be formed, for example, by applying a liquid composition by air spraying, bar coating, dispenser method, brushing, or spatula coating, and then firing in a temperature range of 1100°C or less. In addition, it is preferably formed by a spray coating method (such as a thermal spraying method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method. By using these film formation processes that can be used in a low-temperature range, an electrolyte layer 4 that is dense and has high airtightness and gas barrier properties can be obtained without firing in a high-temperature range exceeding 1100°C, for example. Therefore, damage to the metal substrate 1 can be suppressed, and interdiffusion of elements between the metal substrate 1 and the electrode layer 2 can be suppressed, resulting in an electrochemical element E with excellent performance and durability. In particular, low-temperature firing and spray coating methods are preferred because they allow low-cost elements to be realized. Furthermore, spray coating is even more preferred because it is easy to obtain a dense electrolyte layer with high airtightness and gas barrier properties at a low temperature.

[0139] The electrolyte layer 4 is densely configured to block gas leakage of the anode gas and the cathode gas and to exhibit high ion conductivity. The density of the electrolyte layer 4 is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. When the electrolyte layer 4 is a uniform layer, the density is preferably 95% or more, and more preferably 98% or more. When the electrolyte layer 4 is configured in a multi-layered form, it is preferable that at least a part of the electrolyte layer includes a layer (a dense electrolyte layer) having a density of 98% or more, and more preferably includes a layer (a dense electrolyte layer) having a density of 99% or more. When such a dense electrolyte layer is included in a part of the electrolyte layer, it is easy to form an electrolyte layer that is dense and has high airtightness and gas barrier properties, even when the electrolyte layer is configured in a multi-layered form.

[0140] (Reaction prevention layer) The reaction prevention layer 5 can be formed in a thin layer state on the electrolyte layer 4. When the reaction prevention layer 5 is formed as a thin layer, the thickness can be, for example, about 1 μm to 100 μm, preferably about 2 μm to 50 μm, and more preferably about 4 μm to 25 μm. With such a thickness, it is possible to reduce the amount of expensive reaction prevention layer material used, thereby reducing costs, while ensuring sufficient performance. The material of the reaction prevention layer 5 may be any material that can prevent the reaction between the components of the electrolyte layer 4 and the components of the counter electrode layer 6. For example, a ceria-based material or the like is used. By introducing the reaction prevention layer 5 between the electrolyte layer 4 and the counter electrode layer 6, the reaction between the constituent material of the counter electrode layer 6 and the constituent material of the electrolyte layer 4 is effectively suppressed, and the long-term stability of the performance of the electrochemical element E can be improved. The reaction prevention layer 5 is preferably formed by appropriately using a method that can form the reaction prevention layer 5 at a processing temperature of 1100° C. or less, since it can suppress damage to the metal substrate 1 and also suppress the interdiffusion of elements between the metal substrate 1 and the electrode layer 2, thereby realizing an electrochemical element E with excellent performance and durability. For example, a low-temperature firing method (e.g., a wet method using firing in a low-temperature range without firing in a high-temperature range exceeding 1100°C), a spray coating method (thermal spraying, aerosol deposition, aerosol gas deposition, powder jet deposition, particle jet deposition, cold spray, etc.), a PVD method (sputtering, pulse laser deposition, etc.), a CVD method, etc. can be appropriately used. In particular, the low-temperature firing method and spray coating method are preferable because they allow low-cost elements to be realized. Furthermore, the low-temperature firing method is even more preferable because it makes it easier to handle the raw materials.

[0141] (Counter electrode layer) The counter electrode layer 6 can be formed in a thin layer state on the electrolyte layer 4 or the reaction prevention layer 5. When the counter electrode layer 6 is formed as a thin layer, the thickness can be, for example, about 1 μm to 100 μm, preferably 5 μm to 50 μm. With such a thickness, it is possible to reduce the amount of expensive counter electrode layer material used to reduce costs while ensuring sufficient electrode performance. As the material for the counter electrode layer 6, for example, composite oxides such as LSCF and LSM, ceria-based oxides, and mixtures thereof can be used. In particular, it is preferable that the counter electrode layer 6 contains a perovskite-type oxide containing two or more elements selected from the group consisting of La, Sr, Sm, Mn, Co, and Fe. The counter electrode layer 6 formed using the above materials functions as a cathode.

[0142] The counter electrode layer 6 is preferably formed by a suitable method capable of forming the layer at a processing temperature of 1100° C. or less, since it can suppress damage to the metal substrate 1 and also suppress interdiffusion of elements between the metal substrate 1 and the electrode layer 2, thereby realizing an electrochemical element E having excellent performance and durability. For example, the counter electrode layer 6 can be formed by a suitable method such as a low-temperature firing method (e.g., a wet method using a firing process in a low-temperature range without firing at a high temperature range exceeding 1100° C.), a spray coating method (thermal spraying, aerosol deposition, aerosol gas deposition, powder jet deposition, particle jet deposition, cold spray, etc.), a PVD method (sputtering, pulse laser deposition, etc.), a CVD method, etc. In particular, it is preferable to use a low-temperature firing method or a spray coating method, since it can realize a low-cost element. Furthermore, it is even more preferable to use a low-temperature firing method, since it makes it easier to handle the raw materials.

[0143] (Solid oxide fuel cell) By configuring the electrochemical element E as described above, the electrochemical element E can be used as a power generation cell of a solid oxide fuel cell. For example, a reducing gas (typically a fuel gas containing hydrogen) is supplied to the electrode layer 2 from the rear surface of the metal substrate 1 through the through-holes 1a, and an oxidizing gas (typically air containing oxygen) is supplied to the counter electrode layer 6, which is the counter electrode of the electrode layer 2, and the electrochemical element E is operated at a temperature of, for example, 600°C to 850°C. Then, oxygen O2 contained in the air is converted into electrons e in the counter electrode layer 6. - reacts with oxygen ions O 2- The oxygen ion O 2- In the electrode layer 2, hydrogen H2 contained in the supplied fuel gas is converted into oxygen ions O 2- reacts with water H2O and electrons e - The above reaction generates an electromotive force between the electrode layer 2 and the counter electrode layer 6. In this case, the electrode layer 2 functions as the fuel electrode (anode) of the SOFC, and the counter electrode layer 6 functions as the air electrode (cathode).

[0144] (Method of manufacturing electrochemical device) Next, a method for producing the electrochemical element E according to this embodiment will be described.

[0145] (Metal substrate preparation step) In the metal substrate preparation step, the metal substrate 1 is prepared according to the manufacturing method of the alloy member according to the present invention described above. That is, a plate material made of an Fe-Cr alloy having a predetermined shape is prepared, and a large number of through holes 1a can be formed at predetermined positions of this plate material by laser processing or the like. This plate material is plated according to the method shown in Example 1 or Example 3, and a plating film made of Ni-Co-Mn is formed between the plate material and the outer surface of the base material B.

[0146] (Electrode layer formation step) In the electrode layer forming step, the electrode layer 2 is formed in a thin film state in an area larger than the area where the through holes 1a are provided on the front surface of the metal substrate 1 obtained in the above-mentioned metal substrate preparation step. As described above, the electrode layer 2 can be formed by a low-temperature firing method (a wet method in which firing is performed in a low temperature range of 1100°C or less), a spray coating method (a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, a cold spray method, or the like), a PVD method (a sputtering method, a pulsed laser deposition method, or the like), a CVD method, or the like. Whichever method is used, it is preferable to perform the method at a temperature of 1100°C or less in order to suppress deterioration of the metal substrate 1.

[0147] When the electrode layer formation step is performed by the low-temperature firing method, it is specifically performed as in the following example. First, a material powder of the electrode layer 2 is mixed with a solvent (dispersion medium) to prepare a material paste, which is then applied to the front surface of the metal substrate 1. The electrode layer 2 is then compression molded (electrode layer smoothing step), and fired at 1100°C or lower (electrode layer firing step). The electrode layer 2 can be compression molded by, for example, CIP (Cold Isostatic Pressing), roll pressing, RIP (Rubber Isostatic Pressing), or the like. The electrode layer 2 is preferably fired at a temperature of 800°C or higher and 1100°C or lower. The order of the electrode layer smoothing step and the electrode layer firing step can also be reversed.

[0148] In addition, when forming an electrochemical element having an intermediate layer, the electrode layer smoothing step and the electrode layer firing step can be omitted, or the electrode layer smoothing step and the electrode layer firing step can be included in the intermediate layer smoothing step and the intermediate layer firing step described below. The electrode layer smoothing step can also be performed by lapping, leveling, cutting and polishing the surface, or the like.

[0149] (Diffusion suppression layer formation step) During the firing process in the electrode layer formation step described above, a complex oxide coating 1b (diffusion-suppressing layer (coating layer)) is formed on the surface of the metal substrate 1. If the firing process includes a firing process in which the firing atmosphere is under atmospheric conditions with a low oxygen partial pressure, the interdiffusion of elements is highly suppressed, and a good quality complex oxide coating 1b (diffusion-suppressing layer) with low resistance is formed, which is preferable. The electrode layer formation step may include a separate diffusion-suppressing layer formation step, including a case where a coating method without firing is used. For example, in the separate diffusion-suppressing layer formation step, a complex oxide coating 1b can be formed by applying a Co-containing coating to the base material of the metal substrate 1 and then performing an oxidation treatment.

[0150] In either case, it is preferable to carry out the treatment at a temperature of 1100° C. or less, which is capable of suppressing damage to the metal substrate 1. Furthermore, a complex oxide film 1b may be formed on the surface of the metal substrate 1 during the firing process in the intermediate layer formation step described below.

[0151] (Intermediate layer formation step) In the intermediate layer forming step, the intermediate layer 3 is formed in a thin layer state on the electrode layer 2 so as to cover the electrode layer 2. As described above, the intermediate layer 3 can be formed by a low-temperature firing method (a wet method in which firing is performed in a low temperature range of 1100°C or less), a spray coating method (a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, a cold spray method, or the like), a PVD method (a sputtering method, a pulsed laser deposition method, or the like), a CVD method, or the like. Whichever method is used, it is preferable to perform the method at a temperature of 1100°C or less in order to suppress deterioration of the metal substrate 1.

[0152] When the intermediate layer forming step is performed by the low-temperature firing method, it is specifically performed as follows. First, the material powder of the intermediate layer 3 and a solvent (dispersion medium) are mixed to prepare a material paste, which is then applied to the front surface of the metal substrate 1. The intermediate layer 3 is then compression molded (intermediate layer smoothing step) and fired at 1100°C or less (intermediate layer firing step). The intermediate layer 3 can be rolled by, for example, CIP (Cold Isostatic Pressing), roll pressing, RIP (Rubber Isostatic Pressing), or the like. In addition, it is preferable to fire the intermediate layer at a temperature of 800°C or more and 1100°C or less. This is because such a temperature makes it possible to form a high-strength intermediate layer 3 while suppressing damage and deterioration of the metal substrate 1. In addition, it is more preferable to fire the intermediate layer 3 at 1050°C or less, and even more preferable to fire it at 1000°C or less. This is because the lower the firing temperature of the intermediate layer 3, the more the electrochemical element E can be formed while further suppressing damage and deterioration of the metal substrate 1. Also, the order of the intermediate layer smoothing step and the intermediate layer firing step can be reversed. The intermediate layer smoothing step can also be performed by lapping, leveling, cutting and polishing the surface, or the like.

[0153] (Electrolyte layer formation step) In the electrolyte layer forming step, the electrolyte layer 4 is formed in a thin layer state on the intermediate layer 3 while covering the electrode layer 2 and the intermediate layer 3. Alternatively, the electrolyte layer 4 may be formed in a thin film state having a thickness of 10 μm or less. As described above, the electrolyte layer 4 is preferably formed by a low-temperature baking method (a wet method in which baking is performed at a low temperature range of 1100° C. or less), but can be formed, for example, by applying a coating composition by air spraying, bar coating, dispenser method, brushing, or spatula coating, and baking at a temperature range of 1100° C. or less. Alternatively, a spray coating method (such as a thermal spraying method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method can be used. In any case, it is preferable to perform the method at a temperature of 1100° C. or less in order to suppress deterioration of the metal substrate 1.

[0154] In order to form a high-quality electrolyte layer 4 that is dense and has high airtightness and gas barrier performance in a temperature range of 1100°C or less, it is desirable to perform the electrolyte layer formation step by a spray coating method. In this case, the material for the electrolyte layer 4 is sprayed toward the intermediate layer 3 on the metal substrate 1 to form the electrolyte layer 4. In this case, the material for the electrolyte layer 4 is applied onto the base layer by an air spray method or the like, and the electrolyte layer 4 can be formed by baking at a temperature of 1100°C or less.

[0155] (Reaction prevention layer formation step) In the reaction prevention layer forming step, the reaction prevention layer 5 is formed in a thin layer state on the electrolyte layer 4. As described above, the reaction prevention layer 5 can be formed by low-temperature firing, spray coating (thermal spraying, aerosol deposition, aerosol gas deposition, powder jet deposition, particle jet deposition, cold spray, etc.), PVD (sputtering, pulse laser deposition, etc.), CVD, etc. In any case, it is preferable to perform the method at a temperature of 1100°C or less in order to suppress deterioration of the metal substrate 1. In order to flatten the upper surface of the reaction prevention layer 5, for example, a leveling process or a cutting / polishing process may be performed after the formation of the reaction prevention layer 5, or a press process may be performed after wet formation and before firing.

[0156] (Counter electrode layer formation step) In the counter electrode layer forming step, the counter electrode layer 6 is formed in a thin layer state on the reaction prevention layer 5. As described above, the counter electrode layer 6 can be formed by a low-temperature firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method. Whichever method is used, it is preferable to perform the method at a temperature of 1100° C. or less in order to suppress deterioration of the metal substrate 1.

[0157] In this manner, it is possible to manufacture the electrochemical element E. Note that, by carrying out the above-described electrode layer forming step and intermediate layer forming step, it is possible to manufacture a substrate with an electrode layer for a metal supported electrochemical element.

[0158] In addition, the electrochemical element E may be configured to have either or both of the intermediate layer 3 and the reaction prevention layer 5. That is, the electrode layer 2 and the electrolyte layer 4 may be formed in contact with each other, or the electrolyte layer 4 and the counter electrode layer 6 may be formed in contact with each other. In this case, the intermediate layer forming step and the reaction prevention layer forming step are omitted in the above-mentioned manufacturing method.

[0159] [Electrochemical elements, electrochemical modules, electrochemical equipment] The electrochemical element E, the electrochemical module M, the electrochemical device Y and the energy system Z will be described with reference to FIGS.

[0160] 22, in this form of electrochemical element E, a U-shaped member 7 is attached to the back surface of a metal substrate 1, and the metal substrate 1 and the U-shaped member 7 form a cylindrical support. The U-shaped member 7 (separator) is made of the alloy member described above. When the electrochemical element E is used as a fuel cell, the flow path formed between the metal substrate 1 and the U-shaped member 7 serves as a supply path for a reducing gas (typically a fuel gas containing hydrogen). A plurality of electrochemical elements E are stacked with current collecting members 26 sandwiched therebetween to form an electrochemical module M. The current collecting members 26 are joined to the counter electrode layers 6 of the electrochemical elements E and the U-shaped members 7, electrically connecting them together. Thus, the electrochemical module M is electrically connected as a whole in the stacking direction. The current collecting members 26 are made of the alloy member described above.

[0161] 22, the electrochemical module M has a gas manifold 17, a current collecting member 26, a termination member, and a current drawing section. One open end of the cylindrical support of the electrochemical element E, which is stacked multiple times, is connected to the gas manifold 17 and receives a supply of gas from the gas manifold 17. The supplied gas flows through the inside of the cylindrical support and is supplied to the electrode layer 2 through the through-holes 1a of the metal substrate 1. The gas manifold 17 (manifold) is made of the alloy member described above. At least one of the separator (U-shaped member 7), the manifold (gas manifold 17), and the current collecting member 26 may be made of the above-mentioned alloy member.

[0162] FIG. 23 also shows an overview of the energy system Z and the electrochemical device Y. The energy system Z has an electrochemical device Y and a heat exchanger 53 as a waste heat utilization section that reuses heat discharged from the electrochemical device Y.

[0163] The electrochemical device Y includes an electrochemical module M, a fuel supply unit having a desulfurizer 31 and a reformer 34 (fuel converter) that supplies fuel gas containing a reducing gas to the electrochemical module M, and an inverter 38 that extracts electric power from the electrochemical module M.

[0164] In detail, the electrochemical device Y has a desulfurizer 31, a reforming water tank 32, a vaporizer 33, a reformer 34, a blower 35, a combustion section 36, an inverter 38, a control section 39, a storage container 40 and an electrochemical module M.

[0165] The desulfurizer 31 removes (desulfurizes) sulfur compound components contained in hydrocarbon raw fuel such as city gas. When sulfur compounds are contained in the raw fuel, the provision of the desulfurizer 31 can suppress the effect of the sulfur compounds on the reformer 34 or the electrochemical element E. The vaporizer 33 generates steam from the reforming water supplied from the reforming water tank 32. The reformer 34, which is an example of a fuel reformer, uses the steam generated by the vaporizer 33 to steam reform the raw fuel desulfurized by the desulfurizer 31, and generates a reformed gas containing hydrogen.

[0166] The electrochemical module M generates power by electrochemical reaction using the reformed gas supplied from the reformer 34 and the air supplied from the blower 35. The change in oxygen O2 in the electrochemical element E is shown in Fig. 21. The combustion section 36 mixes the reaction exhaust gas discharged from the electrochemical module M with air and combusts the combustible components in the reaction exhaust gas.

[0167] The electrochemical module M has a plurality of electrochemical elements E and a gas manifold 17. The plurality of electrochemical elements E are arranged in parallel while being electrically connected to each other, and one end (lower end) of the electrochemical elements E is fixed to the gas manifold 17. The electrochemical elements E generate electricity by electrochemically reacting the reformed gas supplied through the gas manifold 17 with air supplied from the blower 35.

[0168] An inverter 38 as a power converter adjusts the output power of the electrochemical module M to the same voltage and frequency as the power received from a commercial grid (not shown). A control unit 39 controls the operation of the electrochemical device Y and the energy system Z.

[0169] The vaporizer 33, the reformer 34, the electrochemical module M, and the combustion section 36 are housed in a storage container 40. The reformer 34 performs a reforming process of the raw fuel (e.g., methane, etc.) by using the combustion heat generated by the combustion of the reaction exhaust gas in the combustion section 36.

[0170] The raw fuel is supplied to the desulfurizer 31 through a raw fuel supply passage 42 by the operation of a boost pump 41. The reforming water in the reforming water tank 32 is supplied to the vaporizer 33 through a reforming water supply passage 44 by the operation of a reforming water pump 43. The raw fuel supply passage 42 merges with the reforming water supply passage 44 at a location downstream of the desulfurizer 31, and the reforming water and raw fuel merged outside the storage container 40 are supplied to the vaporizer 33 provided inside the storage container 40.

[0171] The reforming water is vaporized in the vaporizer 33 to become water vapor. The raw fuel containing water vapor produced in the vaporizer 33 is supplied to the reformer 34 through a water vapor-containing raw fuel supply passage 45. The raw fuel is steam reformed in the reformer 34, which serves as a fuel reformer, to generate a reformed gas containing hydrogen gas as a main component (fuel gas containing hydrogen, which is the reducing gas described above). The reformed gas produced in the reformer 34 is supplied to the gas manifold 17 of the electrochemical module M through a reformed gas supply passage 46.

[0172] The reformed gas supplied to the gas manifold 17 is distributed to the multiple electrochemical elements E and supplied to the electrochemical elements E from the lower end, which is the connection between the electrochemical elements E and the gas manifold 17. Mainly hydrogen in the reformed gas is used for the electrochemical reaction in the electrochemical elements E. Reaction exhaust gas containing the remaining hydrogen gas not used in the reaction is discharged from the upper end of the electrochemical element E to the combustion section 36.

[0173] The reaction exhaust gas is combusted in the combustion section 36 to become combustion exhaust gas, which is discharged to the outside of the storage container 40 from the combustion exhaust gas outlet 50. A combustion catalyst section 51 (e.g., a platinum-based catalyst) is arranged in the combustion exhaust gas outlet 50, and combusts and removes reducing gases such as carbon monoxide and hydrogen contained in the combustion exhaust gas. The combustion exhaust gas discharged from the combustion exhaust gas outlet 50 is sent to a heat exchanger 53 via a combustion exhaust gas exhaust path 52.

[0174] The heat exchanger 53 exchanges heat between the combustion exhaust gas generated by the combustion in the combustion section 36 and the supplied cold water to generate hot water. That is, the heat exchanger 53 operates as a waste heat utilization section that reuses the heat discharged from the electrochemical device Y.

[0175] Instead of the exhaust heat utilization section, a reaction exhaust gas utilization section may be provided that utilizes the reaction exhaust gas discharged (without being combusted) from the electrochemical module M. The reaction exhaust gas contains the remaining hydrogen gas that was not used in the reaction in the electrochemical element E. In the reaction exhaust gas utilization section, the remaining hydrogen gas is utilized for heat utilization through combustion or for power generation using a fuel cell or the like, thereby making effective use of energy.

[0176] [Another embodiment of the electrochemical module] 24 shows another embodiment of the electrochemical module M. The electrochemical module M according to this embodiment is configured by stacking the above-mentioned electrochemical elements E with inter-cell connection members 71 sandwiched therebetween.

[0177] The inter-cell connection member 71 is a plate-like member that is conductive and has no gas permeability, and has grooves 72 formed on the front and back surfaces, the grooves being perpendicular to each other. The inter-cell connection member 71 (interconnector) is made of the above-mentioned alloy member.

[0178] 24, when electrochemical elements E are stacked with this inter-cell connection member 71 sandwiched therebetween, gas can be supplied to the electrochemical elements E through the grooves 72. More specifically, one groove 72 serves as a first gas flow path 72a, and gas is supplied to the front side of the electrochemical element E, i.e., the counter electrode layer 6. The other groove 72 serves as a second gas flow path 72b, and gas is supplied from the back side of the electrochemical element E, i.e., the back surface of the metal substrate 1, to the electrode layer 2 through the through-holes 1a.

[0179] When this electrochemical module M is operated as a fuel cell, an oxidizing gas (typically, air containing oxygen) is supplied to the first gas flow path 72a, and a reducing gas (typically, a fuel gas containing hydrogen) is supplied to the second gas flow path 72b. Then, a reaction as a fuel cell proceeds in the electrochemical element E, and an electromotive force and a current are generated. The generated electric power is taken out of the electrochemical module M from the inter-cell connection members 71 at both ends of the stacked electrochemical elements E.

[0180] In this embodiment, the grooves 72 are formed on the front and back surfaces of the inter-cell connection member 71 so as to be perpendicular to each other. However, the grooves 72 may also be formed on the front and back surfaces of the inter-cell connection member 71 so as to be parallel to each other.

[0181] [Other embodiments] (1) In the above embodiment, the electrochemical element E is used in a solid oxide fuel cell, but the electrochemical element E can also be used in a solid oxide electrolysis cell, an oxygen sensor using a solid oxide, etc. In addition, the alloy member of the present invention can also be used in various devices other than electrochemical elements that require suppression of volatilization of Cr and the like from the members, particularly in various devices that operate in high temperature ranges.

[0182] (2) In the above embodiment, the present invention is used in a metal-supported solid oxide fuel cell using the metal substrate 1 as a support, but the present invention can also be used in an electrode-supported solid oxide fuel cell using the electrode layer 2 or the counter electrode layer 6 as a support, or an electrolyte-supported solid oxide fuel cell using the electrolyte layer 4 as a support. In these cases, the electrode layer 2 or the counter electrode layer 6, or the electrolyte layer 4 can be made to have a required thickness so that it can function as a support.

[0183] (3) In the above embodiment, the electrode layer 2 is made of a composite material such as NiO-GDC, Ni-GDC, NiO-YSZ, Ni-YSZ, CuO-CeO2, or Cu-CeO2, and the counter electrode layer 6 is made of a composite oxide such as LSCF or LSM. The electrochemical element E configured in this manner can be used as a solid oxide fuel cell by supplying hydrogen gas to the electrode layer 2 to make it a fuel electrode (anode) and air to the counter electrode layer 6 to make it an air electrode (cathode). It is also possible to change this configuration and configure the electrochemical element E so that the electrode layer 2 can be made an air electrode and the counter electrode layer 6 can be made a fuel electrode. That is, the electrode layer 2 is made of a composite oxide such as LSCF or LSM, and the counter electrode layer 6 is made of a composite material such as NiO-GDC, Ni-GDC, NiO-YSZ, Ni-YSZ, CuO-CeO2, or Cu-CeO2. In the electrochemical element E configured in this manner, air can be supplied to the electrode layer 2 to make it an air electrode, and hydrogen gas can be supplied to the counter electrode layer 6 to make it a fuel electrode, so that the electrochemical element E can be used as a solid oxide fuel cell.

[0184] (4) In the above embodiment, an example was shown in which the coating film contained Ni, Co, and Mn. However, other elements may be contained in relation to the material layers provided above and below this coating layer.

[0185] (5) In the above embodiment, examples of plating in one step (first and second examples) and two steps (third example) are shown, but, for example, plating containing one element may be performed in three steps. In this case, by plating Ni, Co, and Mn in that order and alloying them by heat treatment, a composite oxide coating containing at least Ni, Co, and Mn can be obtained.

[0186] (6) In addition, the parts where this type of composite oxide film is formed are parts where it is desired to prevent the volatilization of Cr and the like (for example, parts where the above-mentioned oxidizing gases and reducing gases flow and come into direct contact with these gases). It is not necessary for the coating to be provided on the outer surface or entire surface of the Fe-Cr based alloy substrate.

[0187] (7) In the alloy members explained so far, an example has been shown in which a base material B and a plating film b, which is a coating film containing at least the three elements Ni-Co-Mn, are formed. However, the action and effect of suppressing the diffusion and volatilization of Cr and other elements from the base material B can also be obtained by forming an oxide layer of Cr between the base material B and the plating film b containing at least the three elements Ni-Co-Mn.

[0188] In addition, the configurations disclosed in the above embodiments can be applied in combination with the configurations disclosed in other embodiments, as long as no contradiction occurs. Furthermore, the embodiments disclosed in this specification are merely examples, and the present invention is not limited to these embodiments. The present invention can be modified as appropriate within the scope of the present invention. [Explanation of symbols]

[0189] 1 Metal substrate (metal support, alloy component) 1a Through hole 2 electrode layer 3. Middle Tier 4 Electrolyte layer 5. Reaction prevention layer 6 Counter electrode layer 7 U-shaped components (separators, alloy components) 17 Gas manifold (manifold, alloy material) 26 Current collecting material (alloy material) 31 Desulfurizer 32 Reformed water tank 33 Carburetor 34 Reformer (fuel converter) 35 Blower 36 Combustion section 38 Inverter (power converter) 39 Control Unit 40 Storage Container 41 Booster pump 42 Raw fuel supply route 43 Reformed water pump 44 Reformed water supply channel 45 Water vapor-containing raw fuel supply line 46 Reformed gas supply line 50 Combustion exhaust gas outlet 51 Combustion catalyst section 52 Combustion exhaust gas exhaust passage 53 Heat exchanger 71 Inter-cell connection parts (interconnectors, alloy parts) 72 Groove 72a first gas flow path 72b second gas flow path E Electrochemical element M Electrochemistry Module Y Electrochemical Equipment Z Energy System

Claims

1. In order to manufacture an alloy member having a coating film containing at least three elements, Ni, Co, and Mn, formed on the entire or at least a part of the surface of a substrate made of an Fe-Cr alloy, A method for manufacturing an alloy member, comprising forming a plating film as the coating film using a plating solution containing at least three elements of Ni, Co, and Mn.

2. In manufacturing an alloy member having a coating film containing at least three elements of Ni, Co, and Mn formed on all or at least a part of the surface of a substrate of an Fe-Cr alloy, A method for manufacturing an alloy member, comprising forming a multi-layer plating film containing at least the three elements Ni, Co, and Mn through multiple-stage plating using a plating solution containing at least one element selected from the three elements Ni, Co, and Mn, thereby forming a plating film as the coating film.

3. A method for manufacturing an alloy part as described in claim 2, wherein the multi-layer plating film formed in multiple layers contains Mn in the outermost layer located on the outermost side.

4. A method for manufacturing an alloy part as described in claim 2 or 3, wherein the multiple layers are composed of an inner layer located on the substrate side and an outer layer located outside the inner layer, the inner layer containing at least two elements, Ni and Co, and the outer layer containing at least Mn.

5. A method for producing an alloy member having a coating film containing at least three elements of Ni, Co, and Mn formed on all or at least a part of the surface of a substrate of an Fe-Cr alloy, comprising: A method for producing an alloy member, comprising forming an electrodeposition coating film as the coating film using an electrodeposition coating solution containing at least three elements of Ni, Co, and Mn.

6. A method for manufacturing an alloy part according to claim 1, wherein the Fe-Cr alloy contains 0.05 mass % or more of Mn.

7. A method for manufacturing an alloy part described in any one of claims 1 to 6, wherein the Fe-Cr alloy contains Ni in an amount of 0.05 mass% or more and 1.0 mass% or less, Cu in an amount of 0.01 mass% or more and 1.0 mass% or less, and Ti in an amount of 0.05 mass% or more and 1.0 mass% or less.

8. A method for manufacturing an alloy part according to any one of claims 1 to 7, wherein the Fe-Cr alloy contains 18 mass % or more and 25 mass % or less of Cr.

9. A method for manufacturing an alloy member according to claim 1, further comprising the step of: providing a Cr oxide layer between the substrate and the coating film containing at least the three elements Ni, Co and Mn.

10. A method for manufacturing an alloy part according to any one of claims 1 to 5, wherein the coating film is converted into a composite oxide film by heat treatment.

11. A method for manufacturing an alloy part according to claim 1 or 2, wherein after the plating film is formed, Ni, Co, and Mn are diffused into the plating film by heat treatment.

12. A method for manufacturing an alloy member according to any one of claims 1 to 5, further comprising forming the coating film and then diffusing Mn contained in the Fe-Cr alloy into the coating film by heat treatment.

Citation Information

Patent Citations

  • Inter-connector for fuel cell and cell stack

    JP2008077913A

  • Interconnector for solid oxide fuel cell, and method for forming the same

    JP2010250965A

  • Solid oxide fuel battery

    JP2012119126A

  • Interconnector for fuel battery and cell stack using the same

    JP2016189243A

  • Interconnector member and method for manufacturing interconnector member

    JP2021096964A